Electrochemical studies on Alizarin Red S as Negolyte for Redox Flow Battery: A Preliminary Study - Khor, Ai Chia; Mohd Rusllim, Mohamed; K. F., Chong; P. K., Leung (Science Publishing Corporation, 2018)
Redox flow battery (RFB) has received tremendous attention as energy storage system coupled with renewable energy sources. In this